Relationship of Emotional Inteligence and Emotional and Behavior Problems Scales of Children 10-12 Years Old – Parents Report - Fili, Evis (European Journal of Multidisciplinary Studies, 2016)
The present study aimed at investigating the correlation of emotional intelligence total score and three broad band of emotional and behavior problems at 10-12 years old children. It was hypothesized that there will be negative relationship between scales. The sample included 236 children (123 or 52. 1 percent boys and 113 or 47. 9 percent girls), with a mean age of 11 years (SD. 835) (range: 10-12 years). 236 parents participated in the study, 92 of them or 39. 0 percent were mothers, while only 144 of them or 61. 0 percent were fathers. In the chi-square test, there were important differences reported in the distribution of the percentages of parent’s gender and their employment rates. The TEIQue-Child Form questionnaire, contains 75 items responded to on a 5-point scale and measures five distinct facets. Also the CBCL 6-18 years, was used emotional and behavior problems. Descriptive statistics, chi-square test, Pearson correlation, and T-test, were used to explore and analyse the correlations of interest variables in the study on total EI and EB broad band scales. Correlation analysis mostly indicated low and negative but non-significant relationship between EI and EB scales, for all children and by gender. We did not found gender significant differences on EI total scores and EB broad band scale scores.
Keywords: relationship, children, differences, gender, emotional intelligence, emotional and problem behavior, parent.